2011
DOI: 10.1038/nmat2958
|View full text |Cite
|
Sign up to set email alerts
|

Orbital reflectometry of oxide heterostructures

Abstract: arXiv:1101.0238v1 [cond-mat.str-el]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
261
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(282 citation statements)
references
References 34 publications
17
261
3
1
Order By: Relevance
“…From the single-site DMFT calculations with a double-counting energy as another tuning parameter, Wang et al 21 showed that there is a well defined N c , that is, the critical value of d-valency of transition metal; the system is metallic if Relative orbital occupation in the two e g orbitals is a central quantity in understanding LNO/LAO systems 9,12,14,15 . The orbital polarization can be nonzero due to the translation symmetry breaking induced by heterostructuring while the bulk polarization is 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the single-site DMFT calculations with a double-counting energy as another tuning parameter, Wang et al 21 showed that there is a well defined N c , that is, the critical value of d-valency of transition metal; the system is metallic if Relative orbital occupation in the two e g orbitals is a central quantity in understanding LNO/LAO systems 9,12,14,15 . The orbital polarization can be nonzero due to the translation symmetry breaking induced by heterostructuring while the bulk polarization is 0.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most intriguing classes of materials may be the nickelate superlattices [9][10][11][12][13][14][15][16] . A series of recent theoretical studies have created considerable interest, suggesting the heterostructuring-induced orbital polarization and the possible high-T c superconductivity in LaNiO 3 (LAO)/LaAlO 3 (LAO) superlattice 12,17 .…”
mentioning
confidence: 99%
“…11b, 20 There is no shift in the polarization-averaged edge, indicating stoichiometric Ni 3+ with an insignificant amount of oxygen defects in our LNO films ( Supplementary Fig. S9).…”
mentioning
confidence: 82%
“…1,2 This degree of freedom creates a rich variety of behaviors, and a large area in materials science and technology focuses on understanding and controlling these properties (e.g. magnetism, superconductivity, ferroelectricity, etc.)…”
mentioning
confidence: 99%
“…This difference should be detectable by x-ray linear dichroism (XLD) 9,10 or orbital reflectometry. 2 Second, we have explicitly computed and compared tetragonal to that of the BaTiO 3 /LSMO interface, but is quantitatively larger than the orbital polarization of the BaTiO 3 /LSMO interface due to the larger ferroelectric polarization of PbTiO 3 .…”
mentioning
confidence: 99%